Nitrogen Fixation and Nodulation Behaviour of some Nitrogen Fixing Species from Inner and Outer Himalaya - Pokhriyal, T. C.; Chaukiyal, S. P.; Naithani, H. B. (Indian Forester, 1993)
The chances of nitrogenous fertilizer use in various afforestation programmes are very bleak in the near future. The only alternative is to select such species which can meet their nitrogen requirements from soil as well as atmosphere. An attempt has been made in the present study to identify some of the nitrogen fixing herb, shrub and tree species from inner and outer Himalaya region, so that these species can be recommended for the afforestation programmes to a particular area. Out of ninety five species recorded, most of them belong to family leguminosae except Alnus nepalensis and Myrica esculenta non-leguminous.